2015
DOI: 10.1080/00223891.2015.1110824
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validity of the Relationship Profile Test: Links With Measures of Psychopathology and Adult Attachment

Abstract: This study assessed the construct validity of the Relationship Profile Test (RPT; Bornstein & Languirand, 2003) with a substance abuse sample. One hundred-eight substance abuse patients completed the RPT, Experiences in Close Relationships Scale (ECR-SF; Wei, Russell, Mallinckrodt, & Vogel, 2007), Personality Assessment Inventory (PAI; Morey, 1991), and Symptom Checklist-90-Revised (SCL-90-R: Derogatis 1983). Results suggest that the RPT has good construct validity when compared against theoretically related b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 65 publications
(70 reference statements)
0
7
1
1
Order By: Relevance
“…Past results have been attributed to various considerations such as gender-role socialization being predictive of self-reported interpersonal dependency and detachment levels in adolescents and adults (Bornstein, 1996), suggesting the potential for men and women to interpret questions differently or in a manner that impacts ratings for some constructs; however, it can be hard to gauge confounding variables such as specific social roles, emotional reactivity, underlying psychopathology, or cultural differences without specifically testing for them (Abuín and de Rivera, 2015). Our data did not allow for us to test these hypotheses, and, as such, our findings did not reveal any significant differences by gender in RPT scores (Bornstein and Huprich, 2006; Bornstein et al, 2003; Haggerty et al, 2015, 2016). One possible explanation could be due in large part to the heterogeneity of this sample.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Past results have been attributed to various considerations such as gender-role socialization being predictive of self-reported interpersonal dependency and detachment levels in adolescents and adults (Bornstein, 1996), suggesting the potential for men and women to interpret questions differently or in a manner that impacts ratings for some constructs; however, it can be hard to gauge confounding variables such as specific social roles, emotional reactivity, underlying psychopathology, or cultural differences without specifically testing for them (Abuín and de Rivera, 2015). Our data did not allow for us to test these hypotheses, and, as such, our findings did not reveal any significant differences by gender in RPT scores (Bornstein and Huprich, 2006; Bornstein et al, 2003; Haggerty et al, 2015, 2016). One possible explanation could be due in large part to the heterogeneity of this sample.…”
Section: Discussioncontrasting
confidence: 67%
“…Results from a study by Haggerty et al (2010), composed of student participants from a northeastern university, indicated that women's mean DO score was higher than men's, but not for DD or HD. In addition, Haggerty et al (2015, 2016) found no significant differences between genders across all three RPT dimensions in adolescent inpatient and substance abuse populations. In these clinical populations (Haggerty et al, 2015, 2016), effect sizes ( d ; Cohen 1988) between males and females for all RPT subscales ranged from 0.15 to 0.18 (DO), 0.12 to 0.30 (DD), and 0.00 to 0.29 (HD); however, some variation in effect size was noted across RPT studies using undergraduate or nonclinical samples (Abuín and de Rivera, 2015; Bornstein et al, 2002, 2003; Bornstein and Huprich, 2006; Haggerty et al, 2010).…”
Section: Rpt and Gender Differencesmentioning
confidence: 83%
See 1 more Smart Citation
“…Following Bornstein’s (1993) earlier work on dependency, Bornstein et al (2003) developed the Relationship Profile Test (RPT), which has subscales for Destructive Overdependence, Healthy Dependency, and Dysfunctional Detachment, the latter having some overlap with the concept of counterdependency. The RPT has now been validated and compared with other instruments in several different populations (Haggerty et al, 2016). Cooper (1992), in clinical observations of patients struggling with addictions, linked counterdependency to codependency (i.e., a drive to place others’ needs and wants ahead of one’s own), arguing that both result from deficient and pathological “early self-selfobject relations.” Cooper sees counterdependent people as having had unmet needs and wishes to be taken care of in early childhood; they then engage in futile attempts to defend against dependency needs by turning attention away from those needs and instead focusing on the needs of significant others.…”
Section: A Review Of Counterdependency Literaturementioning
confidence: 99%
“…Tal versão foi novamente reaplicada com amostra clínica e não clínicas, que apresentou alfas de 0,87, 0,78 e 0,72, respectivamente. A Relationship Profile Test (RPT)-Teste do Perfil do Relacionamento foi construído por Bornstein, Geiselman, Eisenhart e Languirand (2002), abrangendo três conceitos relacionados à dependência: dependência destrutiva, desprendimento disfuncional e dependência saudável, que apresentaram alfas respectivos de 0,85; 0,85; 0,76, e boa validade de construto, quando comparada a outras medidas já sólidas nesse campo de estudo (Haggerty et al, 2015). Contudo, como apontado por Bornstein et al (2009), maneiras de acessar a validade do instrumento continuamente e sua utilidade em contextos sociais mais abrangentes ainda precisam ser mais claros.…”
Section: Introductionunclassified